Foreign Aid and Recipient Countries' Exports: Does Aid Promote Bilateral Trade? - Felicitas Nowak-Lehmann D.; Inmaculada Martínez-Zarzoso; Adriana Cardozo; Dierk Herzer; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
This paper uses the gravity model of trade to investigate the link between foreign aid and exports in recipient countries. Most of the theoretical work emphasizes the negative impact of aid on recipient countries' exports primarily due to exchange rate appreciation, disregarding possible positive effects of aid in promoting bilateral trade relations. The empirical findings, in contrast, indicate that the net impact of aid on recipient countries' exports is positive -even though the macroeconomic impact of aid is rather small- and that the average return for recipients' exports is about 1.50 US for every aid dollar spent. We argue that 'bilateral aid' seems to promote good bilateral trade relations, mutual trust and familiarity and that those factors reinforce bilateral trade, including recipient country exports. The paper also estimates the effect of different types of aid (bilateral aid versus multilateral aid flowing to a specific recipient) and studies aid's contribution to an expansion of exports in different regions of the world. It is found that aid is strongly export-enhancing in Asia and Latin America, but not in Africa.
Keywords: F10; F35; 330; International trade; foreign aid; recipient exports; bilateral trade relations